ANALISIS DIFERENSIASI CITRA, DIFERENSIASI KUALITAS PELAYANAN, DAN DIFERENSIASI PERSONALIA TERHADAP KEUNGGULAN BERSAING PADA KEDAI KOPI JANJI JIWA DI JAKARTA BARAT - Jeremy Hilman, (2020)
The existence of coffee in Indonesia is currently popular due to the development of coffee shops in several regions in Indonesia. One example of a coffee shop that is popular at millennial times is Janji Jiwa. This research is categorized as quantitative research in which the aim is to determine the effect of image differentiation, service quality differentiation and personnel differentiation on competitive advantage. The population in this study are Janji Jiwa customers or those who have been bought at Janji Jiwa. Samples taken as many as 75 respondents, using probability sampling technique and simple random sampling method. Data collection was done through distributing questionnaires online to respondents. The analysis technique used is the PLS (Partial Least Square) analysis method using SmartPLS 3.0 software. The results of this study indicate that (1) image differentiation has negative and not significant effect on competitive advantage with a path coefficient of 0,081, (2) service quality differentiation has a positive and significant effect on competitive advantage with a path coefficient of 0.385 and (3) personnel differentiation has a positive effect and significant towards competitive advantage with a path coefficient of 0.487. And has an R-Square Adjusted value of 0.848.